Console to Movie Success, Leveraging Nostalgia, and Introducing Subversion in The Super Mario Bros. Movie - Tjokro, Gunawan (Action Research Literate, 2024)
This research examines the success of "The Super Mario Bros. Movie" by leveraging nostalgia and introducing subversion. The adaptation process from video game to film often fails, as seen with previous attempts like "Warcraft" (2016) and "Street Fighter: The Legend of Chun-Li" (2009). However, "The Super Mario Bros. Movie" (2023) succeeded by retaining core elements of the original game while innovatively transforming its narrative and character dynamics. The movie's success is attributed to its nostalgic appeal, faithful yet refreshed character portrayals, and the subversion of traditional gender roles. By making Princess Peach a mentor and strategist and providing Mario a hero's journey from an ordinary plumber to a savior, the film connects with both old fans and new audiences. This study utilizes Andrew Tate's theory of fidelity and transformation, along with perspectives on nostalgia, audience engagement, and gender role subversion, to analyze the movie's reception and success.